2009
DOI: 10.1158/1535-7163.mct-08-1106
|View full text |Cite
|
Sign up to set email alerts
|

Lysophosphatidic acid stimulates cell migration, invasion, and colony formation as well as tumorigenesis/metastasis of mouse ovarian cancer in immunocompetent mice

Abstract: We have already established human xenographic models for the effect of lysophosphatidic acid (LPA) on tumor metastasis in vivo. The purpose of this work is to establish a preclinical LPA effect model in immunocompetent mice. We first characterized the mouse epithelial ovarian cancer (EOC) cell line ID8 for its responsiveness to LPA in cell proliferation, migration, and invasion and compared these properties with those of human EOC. The signaling pathways related to cell migration were further investigated usin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
49
0

Year Published

2010
2010
2018
2018

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 42 publications
(54 citation statements)
references
References 45 publications
5
49
0
Order By: Relevance
“…LPA, a proinflammatory lysophospholipid, is implicated in the etiology of a number of human cancers, including ovarian cancer (14). LPA has been reported to enhance tumor growth of ID8 cells and ascites formation in female C57BL/6 mice (20). We demonstrated that apoA-I and apoA-I mimetic peptides bind LPA, but the apoA-I mimetic peptides bind LPA with an affinity that is six orders of magnitude greater than apoA-I.…”
Section: Apoa-i Mimetic Peptides Inhibit Viability Of Human Ovarian Cmentioning
confidence: 76%
See 2 more Smart Citations
“…LPA, a proinflammatory lysophospholipid, is implicated in the etiology of a number of human cancers, including ovarian cancer (14). LPA has been reported to enhance tumor growth of ID8 cells and ascites formation in female C57BL/6 mice (20). We demonstrated that apoA-I and apoA-I mimetic peptides bind LPA, but the apoA-I mimetic peptides bind LPA with an affinity that is six orders of magnitude greater than apoA-I.…”
Section: Apoa-i Mimetic Peptides Inhibit Viability Of Human Ovarian Cmentioning
confidence: 76%
“…LPA has been identified as an important mediator of tumor development, progression, and metastases in humans (18,19). Li et al recently demonstrated that LPA stimulates cell migration, invasion, and colony formation, as well as tumorigenesis/metastasis of mouse ovarian cancer in immunocompetent mice (20). We have previously demonstrated that apoA-I and apoA-I mimetic peptides bind lipids with high affinity, and apoA-I mimetic peptides are several to four to six orders of magnitude better than apoA-I in binding oxidized lipids (26).We first examined whether apoA-I and L-4F can bind LPA using surface plasmon resonance, as described previously (26).…”
Section: Apoa-i Mimetic Peptides Inhibit Viability Of Human Ovarian Cmentioning
confidence: 99%
See 1 more Smart Citation
“…Closely resembling the LPAeffects in human ovarian cancer cells, LPA induced metastasis of epithelial ovarian cancer in immuno-competent mice [23] .…”
Section: Gpcrs Activated By Bio-active Lipidsmentioning
confidence: 79%
“…Pro-inflammatory and pro-angiogenic lysophospholipids such as lysophosphatidic acid (LPA) have been repeatedly shown to be associated with tumor progression and poor prognosis, and are normally cleared from the serum by apo A-I, which is downregulated in ovarian, gastric and pancreatic cancer patients. Both apo A-I as well as apo A-I mimetic peptides have the ability to bind pro-inflammatory phospholipids like LPA [41], but the apo A-I mimetic peptides bind LPA with a greater affinity than apo A-I, causing their removal from serum and lowering their serum levels. Thus apo A-I controls the rate of cell proliferation in a tumor and the tumor growth [42].…”
Section: Anti Tumor Activity Of Apo A-imentioning
confidence: 99%